A global review of female entrepreneurial finance. (17th March 2021) - Na, HyunJun; Erogul, Murat Sakir
This study examines the external financing sources and decisions of small and medium-sized enterprises (SMEs) across 56 countries and shows how SMEs modify their funding channels in response to economic stage and owner's characteristics. We find that entrepreneurs' personal characteristics including owners' age, gender, and business skills are main determinants for the types of external investor funding available to SMEs. We show that access to external financing for female entrepreneurs is more difficult when they have new technology; moreover, the impact increases significantly in poorer economies. The paper displays at a global scale how SMEs modify their funding channels in response to owner's characteristics such as sex and age. Moreover, it contributes to the literature of female entrepreneurship the connections between gender, age, and economic conditions to the sources of external funding and the decisions female entrepreneurs take in accessing it.